Nature of Turbulence inside Small-scale Magnetic Flux Ropes near the Sun: Parker Solar Probe Observations - Zubair I. Shaikh; Geeta Vichare; Ankush Bhaskar; Anil N. Raghav; Sofiane Bourouaine (The Astrophysical Journal, 2023)
In this study, we probe the turbulence characteristic within the small-scale magnetic flux ropes (SSMFRs) close to the Sun using Parker Solar Probe (PSP) magnetic field data. The study includes 50 SSMFRs observed by PSP during Encounter 1, 2, and 3 between 35.74 R _☉ and 142.29 R _☉ distance from the Sun. We observed that the average spectral index for all the selected SSMFR events is –1.49 ± 0.21. In line with expectations, we also saw average ∣ σ _m ∣ values close to zero throughout the inertial range. We also observed that the size of the eddy at the highest frequency is much smaller than the size of the SSMFRs, indicating anisotropy within it. Thus, our finding supports anisotropic models that feature the Iroshnikov–Kraichnan index. Our findings agree with the turbulence properties of the solar wind near the Sun. We also observe low ∼0.1 compressibility, indicating SSMFRs are dominant by Alfvénic fluctuations. In light of this, we believe such an incompressible MHD spectrum results from nonlinear interactions between Alfvénic fluctuations. As a result, our research contributes to understanding the energy cascade process and its transport in solar plasma within the inner heliosphere.